1998
DOI: 10.2337/diacare.21.6.1008
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Concentrations of Soluble E-Selectin and Vascular Cell Adhesion Molecule-1 in NIDDM: Effect of intensive insulin treatment

Abstract: In poorly controlled NIDDM patients, sE-selectin levels are increased and significantly fall to normal after short-term improvement of glycemic control. This suggests that assaying sE-selectin makes it possible to detect endothelium activation and to follow its reversal with euglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
68
1
3

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 20 publications
13
68
1
3
Order By: Relevance
“…In acute experiments, L-arginine is able to reverse the decreased NO availability induced by acute hyperglycemia in normal subjects. 19 Improved glycemic control obtained with either a 14-day continuous subcutaneous insulin infusion 12 or intensification of dietary or pharmacological treatment 11 reduced the level of the adhesion molecules whose concentration was increased when the glycemic control was poorer. In both studies, however, the posttreatment glycemic level was still elevated (7.5 to 7.8 mmol/L), and the diabetic patients evaluated in those studies had a long-lasting disease (Ϸ10 years).…”
Section: Marfella Et Al Circulating Adhesion Molecules In Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…In acute experiments, L-arginine is able to reverse the decreased NO availability induced by acute hyperglycemia in normal subjects. 19 Improved glycemic control obtained with either a 14-day continuous subcutaneous insulin infusion 12 or intensification of dietary or pharmacological treatment 11 reduced the level of the adhesion molecules whose concentration was increased when the glycemic control was poorer. In both studies, however, the posttreatment glycemic level was still elevated (7.5 to 7.8 mmol/L), and the diabetic patients evaluated in those studies had a long-lasting disease (Ϸ10 years).…”
Section: Marfella Et Al Circulating Adhesion Molecules In Humansmentioning
confidence: 99%
“…4 Type 2 diabetes mellitus is associated with an increased risk of premature atherosclerosis, 5,6 and the circulating levels of some CAMs are higher in the diabetic patient. [7][8][9][10][11][12][13] The relation between plasma glucose or insulin and circulating CAMs is poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most (20,(25)(26)(27)(28)(29), but not all (30,31), studies have shown sVCAM-1 levels to be increased among type 2 diabetic subjects as compared with nondiabetic subjects, and sVCAM-1 levels have been shown to be independently associated with carotid artery intima-media thickness in type 2 diabetes patients (29). In view of these considerations, we investigated the association of sVCAM-1 concentration and risk of cardiovascular and all-cause mortality among nondiabetic and type 2 diabetic subjects in a prospective, populationbased cohort study.…”
mentioning
confidence: 99%
“…Improved metabolic control with insulin, however, was associated with reduced CRP concentration. In a previous study by another group, improved glycaemia with intensive insulin treatment in patients with Type II diabetes was associated with normalisation of initially increased E-selectin [4].…”
mentioning
confidence: 99%